2016
DOI: 10.1186/s12933-016-0433-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucose intolerance after chronic stress is related with downregulated PPAR-γ in adipose tissue

Abstract: BackgroundChronic stress is associated with increased risk of glucose intolerance and cardiovascular diseases, albeit through undefined mechanisms. With the aim of gaining insights into the latter, this study examined the metabolic profile of young adult male rats that were exposed to chronic unpredictable stress.MethodsYoung adult male rats were submitted to 4 weeks of chronic unpredictable stress and allowed to recover for 5 weeks. An extensive analysis including of morphologic, biochemical and molecular par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
1
21
1
Order By: Relevance
“…This may explain the weak association of serum Lcn2 and colonic PPARγ at baseline. Contradictory results on the association of PPARγ and Lcn2 in different organs have been reported [14,22]. The reason(s) for discrepancies is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the weak association of serum Lcn2 and colonic PPARγ at baseline. Contradictory results on the association of PPARγ and Lcn2 in different organs have been reported [14,22]. The reason(s) for discrepancies is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Serum LCN2 has been reported to be elevated and associated with disease activity in patients with IBD [16]. Moreover, the relationship of murine Lcn2 and peroxisome proliferator-activated receptor gamma (PPARγ) in colitis models and lipid studies reveals a relevant intracellular pathway of aberrant Lcn2 expression regulated by PPARγ [17][18][19][20][21][22]. PPARγ is a key nuclear receptor regulating both gut inflammation and mesenchymal stem cell differentiation into osteoblasts [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been suggested that PPAR γ might play a key role in the physiological processes involving both resistin and lipocalin-2/ngal. On the one hand, lipocalin was found to be a selective modulator of PPAR γ activation [ 26 ], and on the other hand, the activation of this factor with a pharmacological agonist (e.g., thiazolidinediones) was found to affect the expression of several adipokines, including resistin [ 27 ]. Of interest, Zoller and colleagues have recently addressed the role of TRAIL in adipogenesis, showing that human recombinant TRAIL was able to interfere with adipogenesis differentiation by downregulating several key adipogenic transcription factors, including PPAR γ , C/EBP α , and C/EBP δ , highlighting an unknown function of TRAIL in the regulation of adipose tissue homeostasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors demonstrated that Lcn-2 significantly promotes human pulmonary artery smooth muscle cell These authors contributed equally: Georgina Hotter, Anna Sola. proliferation by activating the PI3K/Akt-pathway [11]. Furthermore, Lcn-2 is a modulator of peroxisome proliferator-activated receptor (PPAR)-γ activation and has a proven role in lipid homoeostasis and energy expenditure [12,13]. PPAR-γ activation downregulates cell proliferation by inhibiting Akt phosphorylation and its downstream targets [14].…”
Section: Introductionmentioning
confidence: 99%